2022
DOI: 10.1002/advs.202202632
|View full text |Cite
|
Sign up to set email alerts
|

Cilia‐Mediated Insulin/Akt and ST2/JNK Signaling Pathways Regulate the Recovery of Muscle Injury

Abstract: Following injury, skeletal muscle regenerates but fatty tissue accumulation is seen in aged muscle or muscular dystrophies. Fibro/adipogenic progenitors (FAPs) are key players in these events; however, the effect of primary cilia on FAPs remains unclear. Here, it is reported that genetic ablation of trichoplein (TCHP), a ciliary regulator, induces ciliary elongation on FAPs after injury, which promotes muscle regeneration while inhibiting adipogenesis. The defective adipogenic differentiation of FAPs is attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…In this study, we found that overexpression of GPX2 increases JNK, ERK, and p-p38 expression in proliferation process of porcine skeletal muscle cells. Several studies have reported that cell proliferation was promoted via activation of JNK [ 48 , 49 ]. Similar to this, it has been shown that ERK activation mediates cell proliferation and cell cycle progression in myoblasts [ 50 ], and early ERK signal was a crucial factor in determining the proliferation of muscle stem cells [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that overexpression of GPX2 increases JNK, ERK, and p-p38 expression in proliferation process of porcine skeletal muscle cells. Several studies have reported that cell proliferation was promoted via activation of JNK [ 48 , 49 ]. Similar to this, it has been shown that ERK activation mediates cell proliferation and cell cycle progression in myoblasts [ 50 ], and early ERK signal was a crucial factor in determining the proliferation of muscle stem cells [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MAPK signaling pathway were enriched in adipogenic differentiation of FAPs after CLAs treatment. Previous studies have discovered JNK had negative effects on regulating the adipogenic differentiation of human mesenchymal stem cells(Jang et al, 2015) and FAPs could prevent skeletal muscle regeneration after muscle injury by ST2/JNK signaling pathways(Yamakawa et al, 2023). In this study, we found CLAs may promote FAPs directed differentiation into SCD + /DGAT2 + adipocytes via inhibiting JNK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting proteins that can bind and activate AURKA in selective cells may be desirable to maximize therapeutic efficacy and minimize side effects. TCHP may be a candidate for this approach because the knockout mice are viable and show resistance to high-fat diet-induced obesity and increased regeneration following skeletal muscle injuries ( Yamakawa et al, 2021 ; Yamakawa et al, 2022 ). Chemicals can be developed that inhibit the interaction between AURKA and the binding partner or degrade ciliary proteins by proteolysis-targeting chimeras ( Janeček et al, 2016 ; Bagka et al, 2022 ).…”
Section: Ciliogenesis As the Therapeutic Targetmentioning
confidence: 99%